2002
DOI: 10.1046/j.1442-200x.2002.01638.x
|View full text |Cite
|
Sign up to set email alerts
|

Trend of neonatal group B streptococcal infection during the last 15 years

Abstract: The number of GBS-infected cases has stopped increasing, but it is still necessary to carry out screenings of pregnant women for the purpose of decreasing the onset of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 7 publications
2
17
1
Order By: Relevance
“…The majority of erythromycin-and clindamycinresistant GBS were from serotype III, one of the most frequent serotype causing neonatal GBS disease (10,12,14,32). This result differs from previous studies (10)(11)(12)22) that identified serotype V to be associated with erythromycin resistance.…”
Section: Discussioncontrasting
confidence: 80%
“…The majority of erythromycin-and clindamycinresistant GBS were from serotype III, one of the most frequent serotype causing neonatal GBS disease (10,12,14,32). This result differs from previous studies (10)(11)(12)22) that identified serotype V to be associated with erythromycin resistance.…”
Section: Discussioncontrasting
confidence: 80%
“…The light gray areas indicate the additive areas in which the concentrations of L-ficolin and serotype-specific IgG would achieve bactericidal indexes equivalent to those in the corresponding sera (i.e., between 50.4 and 62.5% for serotype III and between 55.0 and 67.9% for serotype V) and k, the FBC index, would be equal to 1. bactericidal index was high, however, and serum opsonized the bacteria effectively, independent of L-ficolin and serotype-specific IgG concentrations. This observation may help explain the discrepancy between the high rate of maternal colonization and the low incidence of early-onset disease associated with serotype VIII in Japan (10,16,23).…”
Section: Discussionmentioning
confidence: 95%
“…agalactiae was the most frequent pathogen for meningitis in infants and small children. Hoshina et al [8] conducted a questionnaire survey of infection by S. agalactiae in Japan, reporting that death or sequelae were noted in 22.6% of early-onset-type cases and 38.7% of delayed-onset-type cases. In this survey, the percentage of patients having sequelae at the end of treatment was high (30.4%) among patients with meningitis caused by this bacterium.…”
Section: Discussionmentioning
confidence: 99%